Zika Virus Infection Induces Elevation of Tissue Factor Production and Apoptosis on Human Umbilical Vein Endothelial Cells - Anfasa, Fatih; Goeijenbier, Marco; Widagdo, Widagdo; Siegers, Jurre Y.; Mumtaz, Noreen; Okba, Nisreen; van Riel, Debby; Rockx, Barry; Koopmans, Marion P. G.; Meijers, Joost C. M.; Martina, Byron E. E. (Frontiers in Microbiology, 2019)
Zika virus (ZIKV) infection is typically characterized by a mild disease presenting with fever, maculopapular rash, headache, fatigue, myalgia and arthralgia. A recent animal study found that ZIKV-infected pregnant Ifnar-/-mice developed vascular damage in the placenta and reduced amount of fetal capillaries. Moreover, ZIKV infection causes segmental thrombosis in the umbilical cord of pregnant rhesus macaques. Furthermore, several case reports suggest that ZIKV infection cause coagulation disorders. These results suggest that ZIKV could cause an alteration in the host hemostatic response, however, the mechanism has not been investigated thus far. This paper aims to determine whether ZIKV infection on HUVECs induces apoptosis and elevation of TF that leads to activation of secondary hemostasis. We infected HUVECs with two ZIKV strains and performed virus titration, immunostaining, and flow cytometry to confirm and quantify infection. We measured tissue factor (TF) concentrations with flow cytometry and performed thrombin generation test (TGT) as a functional assay to assess secondary hemostasis. Furthermore, we determined the amount of cell death using flow cytometry. We also performed enzyme-linked immunosorbent assay (ELISA) to determine interleukin (IL)-6 and IL-8 production and conducted blocking experiments to associate these cytokines with TF expression. Both ZIKV strains infected and replicated to high titers in HUVECs. We found that infection induced elevation of TF expressions. We also showed that increased TF expression led to shortened TGT time. Moreover, the data revealed that infection induced apoptosis. In addition, there was a significant increase of IL-6 and IL-8 production in infected cells. Here we provide in vitro evidence that infection of HUVECs with ZIKV induces apoptosis and elevation of TF expression that leads to activation of secondary hemostasis.